Early Zionists and crusader castles: perceptions and interpretations of crusader material culture, late nineteenth and the early twentieth centuries. Issue 4 (2nd October 2019) - Bronstein, Judith
ABSTRACT: Scholarship analyzing Zionist perceptions of historical remains in Palestine focuses mainly on biblical and Jewish remains. This article analyses responses to material culture which did not fit neatly into Zionist discourse. Crusader remains were a prominent and visible physical presence in the country's cultural landscape, yet they related not to a glorious Jewish past but to a time considered traumatic in Jewish history. This article studies the popular perception and interpretation of these remains by Zionist immigrants and travellers at the end of the nineteenth and beginning of the twentieth century.